Positive electrode composite material, secondary battery, and electric device
The positive electrode composite material with a sustained-release polymer layer addresses cycle stability issues in secondary batteries by enhancing ion transmission and reducing polarization, thereby improving battery performance under high-rate conditions.
Patent Information
- Application Number
- CN202310798475.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Existing secondary batteries face challenges in cycle stability, particularly under high-rate charging and discharging conditions, due to electrode polarization caused by solvent-resistant polymers that hinder ion diffusion.
A positive electrode composite material is developed, featuring a sustained-release polymer layer on the surface of the active material, composed of ester groups, ether bonds, cyano groups, or siloxy groups, which allows for improved ion transmission and reduced polarization, combined with a conductive layer to enhance electronic conduction.
The composite material effectively improves cycle stability and electrochemical performance by facilitating ion transmission and reducing electrode polarization, especially at high rates, through the use of a sustained-release polymer and conductive layer.
Smart Images

Figure CN119230771A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode composite material, a secondary battery and an electrical device. Background Art
[0002] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's performance requirements for secondary batteries have become increasingly higher.
[0003] As the requirements for the battery life of electrical devices continue to increase, there is an urgent need to further improve the cycle stability of secondary batteries. Summary of the invention
[0004] In view of the problems existing in the background technology, the present application provides a positive electrode composite material, aiming to improve the cycle stability of a secondary battery.
[0005] The first aspect of the present application provides a positive electrode composite material, comprising a positive electrode active material and a sustained release layer at least partially coated on the surface of the positive electrode active material, the sustained release layer comprising a sustained release polymer, and the sustained release polymer comprising at least one of an ester group, an ether bond, a cyano group, a benzene ring, and a siloxy group.
[0006] The slow-release polymer coated on the surface of the positive active material can be released from the positive composite material during the use of the positive composite material, so that the polarization of the battery pole piece is reduced, and the metal ions (such as lithium ions) in the active material can be more effectively transmitted, thereby improving the cycle life of the secondary battery. Moreover, compared with being directly formed in the pole piece, the slow-release polymer coated on the surface of the positive active material can more effectively provide an ion transmission channel around the positive active material through its slow-release effect, thereby more significantly improving the cycle performance of the secondary battery at high rates.
[0007] In any embodiment, the sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether, and polydimethylsiloxane.
[0008] In any embodiment, the ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode composite material is 0.55-0.90.
[0009] The ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode composite material within an appropriate range can not only make the positive electrode composite material have good sustained release performance, but also take into account the high loading amount and low resistance of the positive electrode active material, thereby improving the cycle stability of the battery.
[0010] In any embodiment, the average particle size of the positive electrode active material is 60 nm-200 nm, and optionally 80 nm-120 nm.
[0011] The positive electrode active material with an average particle size within a suitable range has both a large specific surface area and a high material structure stability. It can effectively increase the lithium ion deintercalation rate while maintaining the material capacity, thereby improving the electrochemical performance of the secondary battery during rapid charging and discharging, and improving the battery's cycle stability.
[0012] In any embodiment, the thickness of the sustained-release layer is 10 nm-20 nm, and can be optionally 13 nm-18 nm.
[0013] A sustained-release layer of appropriate thickness can not only fully exert the sustained-release effect, but also reduce the increase in resistance caused by excessively thick coating of the sustained-release polymer, thereby improving the cycle stability of the battery through a comprehensive effect.
[0014] In any embodiment, the slow-release polymer is in-situ grown on the surface of the positive electrode active material.
[0015] Compared with the slow-release polymers coated by other methods, the in-situ grown slow-release polymers have stronger adhesion to the positive electrode active materials, the slow-release effect of the slow-release polymers is more lasting, and can more effectively improve the cycle stability of the battery.
[0016] In any embodiment, the positive electrode composite material includes a conductive layer at least partially coated on the surface of the sustained-release layer.
[0017] Further compounding of the conductive layer can increase the electronic conduction rate of the positive electrode composite material, optimize the electrochemical performance of the battery, especially at high rates, and improve the cycle stability of the battery.
[0018] In any embodiment, based on the total mass of the positive electrode composite material, the mass percentage of the conductive layer is 4%-15%, and optionally 6%-12%.
[0019] The mass percentage of the conductive layer within an appropriate range can take into account both the high electron transmission capacity and high load of the electrode, thereby improving the cycle stability of the battery.
[0020] In any embodiment, the conductive layer comprises graphene.
[0021] Graphene is a sp 2A new material in which hybrid connected carbon atoms are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. It can be understood that graphene can be either a single-layer graphene or a nano-layer composed of multiple layers of graphene. The positive electrode active material is inserted into the graphene sheet of the two-dimensional sheet structure, so that the positive electrode composite material has a sandwich structure. The positive electrode composite material with a sandwich structure can use the sheet structure of graphene to provide an effective path for the transmission of lithium ions, and more effectively improve the cycle stability of the battery.
[0022] The second aspect of the present application provides a method for preparing a positive electrode composite material, the preparation method comprising the following steps: providing a positive electrode active material, coating a slow-release polymer on at least a portion of the surface of the positive electrode active material, the slow-release polymer comprising at least one of an ester group, an ether bond, a cyano group, a benzene ring, and a siloxy group.
[0023] In any embodiment, the method of coating at least a portion of the surface of the positive electrode active material with a sustained-release polymer specifically includes: mixing an emulsifier, an aqueous solvent, an oil phase solvent, a positive electrode active material, an initiator and the monomer, and preparing an emulsion containing the positive electrode composite material by emulsion polymerization, wherein the monomer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring, and a siloxy group.
[0024] In any embodiment, the preparation method further comprises the following step: coating at least a portion of the surface of the sustained-release polymer with a conductive layer.
[0025] The third aspect of the present application provides a secondary battery, including a positive electrode plate and an electrolyte, the positive electrode plate includes a positive electrode composite material, the positive electrode composite material includes a positive electrode active material and a sustained release layer at least partially coated on the surface of the positive electrode active material, the sustained release layer includes a sustained release polymer, the sustained release polymer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group, and the sustained release polymer can be dissolved in the electrolyte during the cycle of the secondary battery.
[0026] During the charge and discharge cycle of the secondary battery, the electrolyte will repeatedly infiltrate the positive electrode sheet and repeatedly squeeze out of the positive electrode sheet as the battery expands and contracts. Under the infiltration of the electrolyte, the slow-release polymer in the slow-release layer of the positive electrode composite material will be released from the positive electrode sheet under stress and dissolved in the electrolyte, so that the polarization of the positive electrode sheet is reduced, and the active ions (such as lithium ions) in the active material can be more effectively transmitted, thereby improving the cycle life of the secondary battery. Compared with the slow-release polymer directly formed in the electrode sheet, the slow-release polymer coated on the surface of the positive electrode active material can provide an ion transmission channel around the positive electrode active material more effectively through its dissolution, thereby more significantly improving the cycle performance of the secondary battery at high rates.
[0027] In any embodiment, the sustained-release polymer comprises an ester group, and the electrolyte comprises an ester solvent.
[0028] Both the sustained-release polymer and the ester solvent contain ester functional groups, and the solubility parameters of the two are similar, and they have good compatibility, which is beneficial to improving the sustained-release effect of the sustained-release polymer.
[0029] In any embodiment, at 20°C to 25°C, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no greater than 2J 1 / 2 / cm 3 / 2 .
[0030] At 20℃~25℃, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no more than 2J 1 / 2 / cm 3 / 2 The molecular chain of the slow-release polymer is easy to diffuse in the solvent, that is, the slow-release polymer has good solubility in the solvent of the electrolyte. The slow-release polymer released from the electrode can be dissolved in the solvent of the electrolyte, reducing the negative impact on the subsequent cycles of the battery.
[0031] In any embodiment, the sustained-release polymer comprises at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether or polydimethylsiloxane.
[0032] In any embodiment, the viscosity of the electrolyte is 0.8 mPa·s-1.50 mPa·s, and can be optionally 1.03 mPa·s-1.09 mPa·s.
[0033] The viscosity of the electrolyte is within an appropriate range so that the electrolyte maintains good ionic conductivity, further reduces electrode polarization, and improves the cycle performance of the battery, especially the cycle stability at high rates.
[0034] In any embodiment, a secondary battery includes the positive electrode composite material of the first aspect of the present application.
[0035] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0037] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0038] Figure 3FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0039] Reference numerals:
[0040] 1 battery pack; 2 upper box; 3 lower box; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0041] Hereinafter, the embodiments of the positive electrode composite material, secondary battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0042] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0047] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0048] In the prior art, in order to ensure the battery life, the binder in the pole piece usually adopts a solvent-resistant polymer, that is, the binder in the pole piece cannot be dissolved in the solvent of the electrolyte, such as a polymer with poor compatibility with the solvent of the electrolyte, a cross-linked polymer, etc. A cross-linked polymer refers to a network polymer or polymer formed by chemical bonds between polymer chains. The cross-linking reaction can occur during the polymerization reaction, or a chemical reaction can be used to cross-link the linear polymer after the polymer is formed. The cross-linked polymer has the characteristics of being insoluble and infusible. When the degree of cross-linking is low, the cross-linked polymer can swell in the solvent. As the degree of cross-linking increases, the swelling degree of the cross-linked polymer decreases, and the solvent resistance is enhanced.
[0049] Although solvent-resistant polymers help to maintain the positive electrode active materials on the electrode sheets for a long time, they will also hinder the diffusion of active ions (such as lithium ions and sodium ions) on the positive electrode sheets, which is not conducive to the deintercalation of active ions in the positive electrode active materials. Especially under high temperature or high-rate charging and discharging conditions, the electrode polarization increases significantly with the increase of current density, and the active ions cannot be quickly embedded / embedded, resulting in a decrease in the reversible capacity of the battery and a decrease in the cycle stability.
[0050] [Cathode composite material]
[0051] Based on this, the present application provides a positive electrode composite material, which includes a positive electrode active material and a sustained release layer at least partially coated on the surface of the positive electrode active material, the sustained release layer includes a sustained release polymer, and the sustained release polymer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group.
[0052] The sustained-release polymer refers to a polymer that can be released from the positive electrode composite material during the use of the positive electrode composite material.
[0053] In some embodiments, the sustained release polymer does not include a cross-linked polymer.
[0054] After cross-linking, the polymer becomes insoluble and infusible, making it difficult to exert a sustained-release effect.
[0055] In some embodiments, the sustained-release polymer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring, and a siloxy group.
[0056] The above functional groups make the polymer have high cohesion and adhesion, and can form a film on the surface of the positive electrode active material under the action of molecular forces without the help of a cross-linking agent.
[0057] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material of a lithium secondary battery may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2(Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0058] The morphology of the cathode composite material can be characterized by cross-sectional observation of the material using a scanning electron microscope.
[0059] The slow-release polymer coated on the surface of the positive active material can be released from the positive composite material during the use of the positive composite material, so that the polarization of the battery pole piece is reduced, and the metal ions (such as lithium ions) in the active material can be more effectively transmitted, thereby improving the cycle life of the secondary battery. Moreover, compared with being directly formed in the pole piece, the slow-release polymer coated on the surface of the positive active material can provide an ion transmission channel around the positive active material through its slow-release effect more effectively, thereby more significantly improving the cycle performance of the secondary battery at high rates. The slow-release polymer including ester groups, ether bonds, cyano groups, benzene rings, and siloxy groups not only has a good slow-release effect during use, but also has high bonding force, mechanical strength, and chemical stability, can play the role of a binder when the pole piece is formed, can play a slow-release role when the battery is used, and optimizes the cycle stability of the battery.
[0060] In some embodiments, the sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether, or polydimethylsiloxane.
[0061] In some embodiments, the ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode composite material is 0.55-0.90.
[0062] In some embodiments, the ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode composite material may be 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 or any value therebetween.
[0063] The average particle size of the positive electrode active material and the average particle size of the positive electrode composite material can be tested by any method known in the art, such as measuring the particle size of the material using a scanning electron microscope and calculating the average value.
[0064] The ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode composite material within an appropriate range can not only make the positive electrode composite material have good sustained release performance, but also take into account the high loading amount and low resistance of the positive electrode active material, thereby improving the cycle stability of the battery.
[0065] In some embodiments, the average particle size of the positive electrode active material is 60 nm-200 nm, and optionally 80 nm-120 nm.
[0066] In some embodiments, the average particle size of the positive electrode active material may be selected to be 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or any value therebetween.
[0067] The positive electrode active material with an average particle size within a suitable range has both a large specific surface area and a high material structure stability. It can effectively increase the lithium ion deintercalation rate while maintaining the material capacity, thereby improving the electrochemical performance of the secondary battery during rapid charging and discharging, and improving the battery's cycle stability.
[0068] In some embodiments, the thickness of the sustained-release layer is 10 nm-20 nm, and can be 13 nm-18 nm.
[0069] In some embodiments, the thickness of the sustained-release layer may be 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or any value therebetween.
[0070] The thickness of the sustained-release layer can be tested by any method known in the art, such as measuring the thickness of the sustained-release layer using a scanning electron microscope.
[0071] A sustained-release layer of appropriate thickness can not only fully exert the sustained-release effect, but also reduce the increase in resistance caused by excessively thick coating of the sustained-release polymer, thereby improving the cycle stability of the battery through a comprehensive effect.
[0072] In some embodiments, the slow-release polymer is in-situ grown on the surface of the positive electrode active material.
[0073] In some embodiments, the sustained-release polymer takes the positive electrode active material as the core, and the sustained-release polymer monomers are in situ polymerized on the surface thereof.
[0074] Compared with the slow-release polymers coated by other methods, the in-situ grown slow-release polymers have stronger adhesion to the positive electrode active materials, the slow-release effect of the slow-release polymers is more lasting, and can more effectively improve the cycle stability of the battery.
[0075] In some embodiments, the positive electrode composite material includes a conductive layer at least partially coated on the surface of the sustained-release layer.
[0076] In some embodiments, the conductive layer comprises a conductive carbon material.
[0077] Further compounding of the conductive layer can increase the electronic conduction rate of the positive electrode composite material, optimize the electrochemical performance of the battery, especially at high rates, and improve the cycle stability of the battery.
[0078] In some embodiments, the conductive layer includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0079] In some embodiments, the conductive layer includes graphene.
[0080] In some embodiments, the positive electrode composite material is in a sandwich structure.
[0081] Graphene is a sp 2 A new material in which hybrid connected carbon atoms are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. It can be understood that graphene can be either a single-layer graphene or a nano-layer composed of multiple layers of graphene. The positive electrode active material is inserted into the graphene sheet of the two-dimensional sheet structure, so that the positive electrode composite material has a sandwich structure. The positive electrode composite material with a sandwich structure can use the sheet structure of graphene to provide an effective path for the transmission of lithium ions, and more effectively improve the cycle stability of the battery.
[0082] In some embodiments, based on the total mass of the positive electrode composite material, the mass percentage of the conductive layer is 4%-15%, and optionally 6%-12%.
[0083] In some embodiments, based on the total mass of the positive electrode composite material, the mass content of the conductive layer can be selected to be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value therebetween.
[0084] The mass percentage of the conductive layer within an appropriate range can take into account both the high electron transmission capacity and high load of the electrode, thereby improving the cycle stability of the battery.
[0085] The second aspect of the present application provides a method for preparing a positive electrode composite material, the preparation method comprising the following steps: providing a positive electrode active material, coating a slow-release polymer on at least a portion of the surface of the positive electrode active material, the slow-release polymer comprising at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group.
[0086] In some embodiments, the positive electrode active material is used as a core, and monomers are polymerized in situ to prepare a sustained-release polymer that at least partially covers the surface of the positive electrode active material to obtain a positive electrode composite material.
[0087] In some embodiments, the positive electrode active material is used as a core, and a sustained-release polymer is coated on at least a portion of the surface of the positive electrode active material by physical mixing to obtain a positive electrode composite material.
[0088] In some embodiments, the method of coating at least a portion of the surface of the positive electrode active material with a sustained-release polymer specifically includes: mixing an emulsifier, an aqueous solvent, an oily solvent, a positive electrode active material, an initiator and the monomer, and preparing an emulsion containing the positive electrode composite material by emulsion polymerization, wherein the monomer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group.
[0089] In some embodiments, the mixed emulsifier, aqueous solvent, oil-phase solvent, positive electrode active material, initiator and the monomer specifically include: mixing the emulsifier, aqueous solvent, and oil-phase solvent to obtain an emulsion system, mixing the emulsion system with the positive electrode active material to obtain a mixed system; mixing the initiator, the monomer and the mixed system to obtain a reaction system.
[0090] In some embodiments, the aqueous solvent includes water and a mixed solution of water.
[0091] In some embodiments, the oil phase solvent mainly refers to a solvent capable of dissolving non-polar molecules, such as a hydrocarbon solvent, an ether solvent, or an ester solvent. In some embodiments, the oil phase solvent includes n-hexane.
[0092] Compared with traditional emulsion polymerization, the emulsion system provided in the present application has higher stability, can achieve dispersion of positive electrode active materials in latex particles, and helps to increase the coverage rate of sustained-release polymer on positive electrode active materials.
[0093] In some embodiments, the emulsifier includes at least one of polyethylene glycol octylphenyl ether Triton X-100, sodium lauryl sulfate, and sorbitan monooleate polyoxyethylene ether T-80.
[0094] In some embodiments, the volume content of the emulsifier is 15%-20% based on the total volume of the emulsion system.
[0095] Different from traditional emulsion polymerization, the preparation method of the present application has a high emulsifier content, which makes the emulsion system more stable.
[0096] In some embodiments, the emulsion system further includes an emulsifier. Optionally, the emulsifier includes an alcohol solvent.
[0097] In some embodiments, the initiator comprises a water-soluble initiator. Alternatively, the initiator comprises a persulfate.
[0098] In some embodiments, the monomer includes at least one of styrene, methyl methacrylate, and acrylonitrile.
[0099] In some embodiments, the reaction conditions of the emulsion polymerization are 50° C.-75° C. for 1 h-2 h, then the temperature is raised to 75° C.-90° C. for 3 h-6 h.
[0100] In some embodiments, after adjusting the reaction conditions to the reaction conditions of the emulsion polymerization, the initiator, the monomer and the mixed system are mixed.
[0101] In some embodiments, providing the positive electrode active material specifically includes: preparing the positive electrode active material by a sol-gel method, and the average particle size of the positive electrode active material is 60nm-200nm, and can be 80nm-120nm.
[0102] The positive electrode active material prepared by the sol-gel method has a small particle size and high purity, and is easy to achieve in-situ coating of the sustained-release polymer on its surface.
[0103] The sol-gel method refers to using compounds containing highly chemically active components as precursors, uniformly mixing the raw materials in the liquid phase, and conducting hydrolysis and condensation chemical reactions to form a stable transparent sol system in the solution. After aging, the sol particles slowly polymerize to form a gel with a three-dimensional network structure. The gel network is filled with solvents that have lost their fluidity to form a gel. The gel is dried, sintered and solidified to prepare molecular and even nanostructured materials.
[0104] In some embodiments, the preparation method further comprises the following step: coating a conductive layer on at least a portion of the surface of the sustained-release polymer.
[0105] In some embodiments, the positive electrode active material includes a lithium-containing phosphate.
[0106] The third aspect of the present application provides a secondary battery, including a positive electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode composite material, the positive electrode composite material includes a positive electrode active material and a sustained release layer at least partially coated on the surface of the positive electrode active material, the sustained release layer includes a sustained release polymer, the sustained release polymer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring, and a siloxy group, and the sustained release polymer can be dissolved in the electrolyte during the cycle of the secondary battery.
[0107] During the charge and discharge cycle of the secondary battery, the electrolyte will repeatedly infiltrate the positive electrode sheet and repeatedly squeeze out of the positive electrode sheet as the battery expands and contracts. Under the infiltration of the electrolyte, the slow-release polymer in the slow-release layer of the positive electrode composite material will be released from the positive electrode sheet under stress and dissolved in the electrolyte, so that the polarization of the positive electrode sheet is reduced, and the active ions (such as lithium ions) in the active material can be more effectively transmitted, thereby improving the cycle life of the secondary battery. Compared with the slow-release polymer directly formed in the electrode sheet, the slow-release polymer coated on the surface of the positive electrode active material can provide an ion transmission channel around the positive electrode active material more effectively through its dissolution, thereby more significantly improving the cycle performance of the secondary battery at high rates.
[0108] In some embodiments, the sustained-release polymer includes an ester group. As an example, the sustained-release polymer including an ester group includes, but is not limited to, block copolymers of polymethyl methacrylate, polyethyl methacrylate, polypropyl methacrylate, polyn-butyl methacrylate, polyt-butyl methacrylate, polyn-hexyl methacrylate, polylauryl methacrylate, polyisobornyl methacrylate, polyoctadecyl methacrylate, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, and polymethyl methacrylate-propylene sulfite.
[0109] In some embodiments, the sustained-release polymer comprises an ether bond. As an example, the sustained-release polymer comprising an ether bond includes, but is not limited to, polyethylene oxide and polypropylene oxide.
[0110] In some embodiments, the electrolyte includes at least one of an ester solvent and an ether solvent. An ester solvent refers to an ester compound that can be used as a solvent. An ether solvent refers to an ether compound that can be used as a solvent.
[0111] In some embodiments, the ester solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, and 1,4-butyrolactone.
[0112] In some embodiments, the ether solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol formate ethyl ether, ethylene glycol dibutyl ether, 1,3-dioxolane, 1,4-dioxane, tetrahydrofuran, methyltetrahydrofuran, 1,1,2,2-tetrafluoroethyl methyl ether, 2,2,3,3-tetrafluoropropyl methyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, bis-(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl nonafluorobutyl ether, bis-(1,1,2,2-tetrafluoroethyl) ether, and difluoromethyl-2,2,2-trifluoroethyl ether.
[0113] In some embodiments, the sustained-release polymer includes an ester group; and the electrolyte includes an ester solvent.
[0114] In some embodiments, the sustained-release polymer includes a block copolymer of polymethyl methacrylate and propylene sulfite, and the electrolyte includes an ester solvent.
[0115] Both the ester polymer and the ester solvent contain ester functional groups, and the solubility parameters of the two are similar, and they have good compatibility, which is beneficial to improving the sustained release effect of the sustained release polymer. In some embodiments, the sustained release polymer includes polymethyl methacrylate, and the electrolyte includes an ester solvent.
[0116] In some embodiments, the sustained-release polymer includes an ether polymer; and the electrolyte includes an ether solvent.
[0117] In some embodiments, the sustained-release polymer includes polyethylene oxide, and the electrolyte includes an ether solvent.
[0118] Both ether polymers and ether solvents contain ether bonds, have similar solubility parameters, and have good compatibility, which is beneficial to improving the sustained-release effect of the sustained-release polymer.
[0119] In some embodiments, the sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether, or polydimethylsiloxane.
[0120] In some embodiments, at 20°C to 25°C, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no greater than 2J 1 / 2 / cm 3 / 2 .
[0121] The solubility parameter δ is often used to characterize the miscibility between different substances. The solubility parameter δ can be expressed as follows:
[0122]
[0123] Where ΔE is the cohesive energy of the substance, in J; V is the molar volume of the substance, in cm 3 According to the principles of thermodynamics, the greater the difference in solubility parameters δ between two substances, the greater the change in system enthalpy after the two substances are mixed, and the probability of the system reaching thermodynamic compatibility also decreases. A small difference in solubility parameters between different substances is conducive to improving the solubility between substances.
[0124] The solubility parameter can be measured by any method in the art. As an example, the solubility parameter can be measured by the intrinsic viscosity method. Prepare solvents with different solubility parameter values, measure the intrinsic viscosity of the sustained-release polymer in these solvents respectively, plot the intrinsic viscosity against the solubility parameter of the corresponding solvent, and take the solubility parameter value corresponding to the maximum intrinsic viscosity as the solubility parameter value of the polymer. The intrinsic viscosity refers to the limit value of the reduced viscosity or the reduced logarithmic viscosity of an infinitely diluted polymer solution. The intrinsic viscosity can be measured by any known method in the art. As an example, the intrinsic viscosity can be measured by the dilution method specified in the national standard GB / T12005.1-1989.
[0125] It can be understood that the sustained-release polymer may include only one polymer or multiple polymers. The solvent of the electrolyte may include only one solvent compound or multiple solvent compounds.
[0126] At 20℃~25℃, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no more than 2J 1 / 2 / cm 3 / 2 The molecular chain of the slow-release polymer is easy to diffuse in the solvent, that is, the slow-release polymer has good solubility in the solvent of the electrolyte. The slow-release polymer released from the electrode can be dissolved in the solvent of the electrolyte, reducing the negative impact on the subsequent cycles of the battery.
[0127] In some embodiments, the viscosity of the electrolyte is 0.8 mPa·s-1.50 mPa·s, and can be optionally 1.03 mPa·s-1.09 mPa·s.
[0128] In some embodiments, the viscosity of the electrolyte may be 0.80 mPa·s, 0.85 mPa·s, 1 mPa·s, 1.03 mPa·s, 1.09 mPa·s, 1.20 mPa·s, or 1.50 mPa·s.
[0129] The viscosity of the electrolyte can be measured by any known method in the art. As an example, the viscosity of the electrolyte can be measured using a rotational viscometer.
[0130] The viscosity of the electrolyte is within an appropriate range so that the electrolyte maintains good ionic conductivity, further reduces electrode polarization, and improves the cycle performance of the battery, especially the cycle stability at high rates.
[0131] In some embodiments, the secondary battery includes at least one of a lithium secondary battery, a sodium secondary battery, a magnesium secondary battery, and a potassium secondary battery.
[0132] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode film layer, and the positive electrode film layer includes a positive electrode composite material.
[0133] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0134] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0135] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0136] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0137] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode composite material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0138] [Negative electrode]
[0139] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0140] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0141] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0142] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0143] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0144] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0145] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0146] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0147] [Isolation film]
[0148] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0149] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0150] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0151] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0152] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0153] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0154] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0155] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0156] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0157] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0158] Figure 3 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0159] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0160] The present application also provides a use of a polymer, which is used as a sustained-release polymer in a positive electrode composite material of any embodiment or a secondary battery of any embodiment. Optionally, the polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether, and polydimethylsiloxane.
[0161] Example
[0162] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0163] 1. Preparation method
[0164] Example 1
[0165] 1) Preparation of positive electrode composite materials
[0166] Using the conventional sol-gel method, CH 3 COOLi, Fe(CH 3 COO 2 , H 3 PO 4 and C 6 H 10 O 4 The solution was dissolved in ethanol according to the stoichiometric ratio, wherein n(P):n(Fe):n(Li)=1:1:1.03, and was fully mixed with aqueous adipic acid as a chelating agent. The solution was evaporated at 90°C for 4 hours to form a transparent sol; the sol was then dried in a vacuum oven at 90-100°C for 24 hours to obtain a gel precursor. The gel precursor was ground and calcined at 400°C for 1.5 hours, and then calcined at 670°C in an Ar atmosphere using a tube furnace for 2.5 hours to obtain LiFePO 4 (LFP) nanoparticles with an average volume particle size of 100 nm.
[0167] A solution of polyethylene glycol octylphenyl ether (Triton X-100), n-butanol, cyclohexane and deionized water was prepared in a volume ratio of 3:1:5:7. 2.5 g of the prepared LFP nanoparticles were added to the above solution and the mixture was stirred, refluxed and heated under N 2 The reactor at the inlet was stirred thoroughly. At 70°C, 0.15 g of initiator ammonium persulfate (APS) was added, and 1.25 g of methyl methacrylate monomer was quickly added dropwise. After reacting for 1.5 h, the temperature was raised to 80°C and polymerized for another 4 h to prepare an emulsion of LFP@PMMA composite material with LFP as the core and polymethyl methacrylate (PMMA) as the shell.
[0168] The obtained emulsion was filtered and dried to obtain the LFP@PMMA cathode composite material.
[0169] 2) Preparation of positive electrode
[0170] The prepared positive electrode composite material, conductive agent acetylene black, and binder PVDF were mixed in a weight ratio of 94:4:2, and solvent N-methylpyrrolidone was added, and the mixture was stirred and mixed to obtain a positive electrode slurry, which was then coated on both surfaces of the positive electrode current collector aluminum foil. The coating weight of the positive electrode slurry was 0.224 g / 1540.25 mm 2 (measured in terms of solid content), and then dried and cold pressed to obtain the positive electrode sheet.
[0171] 3) Preparation of negative electrode sheet
[0172] The negative electrode active material artificial graphite (gram capacity of 340 mAh / g), the conductive agent acetylene black, styrene butadiene rubber (SBR), and carboxymethyl cellulose CMC were mixed in a weight ratio of 95:1.5:3.1:0.4, and the solvent deionized water was added, and the mixture was stirred and mixed to obtain a negative electrode slurry, which was then coated on both surfaces of the negative electrode current collector copper foil, wherein the coating weight of the negative electrode slurry was 0.108 g / 1540.25 mm 2 (based on solid content), and after drying and cold pressing, the negative electrode sheet is obtained.
[0173] 4) Preparation of electrolyte
[0174] In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), polycarbonate (PC), and dimethyl carbonate (DMC) were mixed at a mass ratio of EC:PC:DMC=3:3:3, and then LiPF 6 , vinyl carbonate (VC), vinyl sulfate (DTD), 1,3-propane sultone are added to a mixed organic solvent and stirred to obtain an electrolyte, wherein LiPF 6 The concentration in the electrolyte is 1 mol / L, and the mass percentages of VC, DTD, and 1,3-propane sultone are 3%, 1%, and 1%, respectively.
[0175] 5) Isolation film
[0176] A polyethylene film (PE membrane) is used as the isolation membrane.
[0177] 6) Preparation of batteries
[0178] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, the prepared electrolyte is injected, and the package is packaged for formation to obtain a lithium secondary battery.
[0179] In Example 2, the type of sustained-release polymer was adjusted to polystyrene (PS), and the monomer added during the polymerization was 1.25 g of styrene. The rest was the same as in Example 1.
[0180] In Example 3-4, a conductive layer is coated outside the sustained-release layer of the positive electrode composite material, and the rest is the same as in Example 1. The specific parameters are shown in Table 1. The preparation method of the positive electrode composite material coated with the conductive layer in Example 4 is:
[0181] A solution of polyethylene glycol octylphenyl ether (Triton X-100), n-butanol and cyclohexane was prepared in a volume ratio of 3:1:5. 2.5 g of the prepared LFP nanoparticles were added to the above solution and the mixture was stirred, refluxed and heated under N 2The reactor at the inlet was stirred thoroughly. At 70°C, 0.15 g of initiator ammonium persulfate (APS) was added, and 1.25 g of methyl methacrylate monomer was quickly added dropwise. After reacting for 1.5 h, the temperature was raised to 80°C and polymerized for another 4 h to prepare an LFP@PMMA composite latex containing LFP as the core and polymethyl methacrylate (PMMA) as the shell.
[0182] Anhydrous ethanol was added to the mixed graphene solution in the emulsion, wherein the mass ratio of LFP@PMMA composite material in the emulsion to graphene in the graphene solution was 91:9, and then stirred for 12 hours to obtain a suspension, and then the product was allowed to stand for 1 hour, and the obtained emulsion was filtered and dried to obtain a graphene / LFP@PMMA / graphene sandwich structure positive electrode composite material.
[0183] In Example 3, the conductive material is changed from graphene to super carbon black (super P).
[0184] In Examples 5-8, the calcination time of the gel precursor was adjusted to make the volume average particle size of the positive electrode active material different. The specific parameters are shown in the table. Other parameters are the same as in Example 4.
[0185] In Examples 9-12, the amount of methyl methacrylate monomer added was adjusted so that the thickness of the sustained-release layer was different. The specific parameters are shown in the table, and the others are the same as in Example 4. In Example 9, 0.80 g of methyl methacrylate was added so that the thickness of the sustained-release layer was 10 nm; in Example 10, 1.56 g of methyl methacrylate was added so that the thickness of the sustained-release layer was 20 nm; in Example 11, 1.02 g of methyl methacrylate was added so that the thickness of the sustained-release layer was 13 nm; in Example 12, 1.40 g of methyl methacrylate was added so that the thickness of the sustained-release layer was 18 nm. In Examples 13-16, the amount of conductive material added was adjusted so that the mass content of the conductive layer was different. The specific parameters are shown in the table, and the others are the same as in Example 4.
[0186] In Example 17, the preparation method of the sustained-release layer is not in-situ polymerization, but coating on the positive electrode active material through a blending process. The specific preparation method is:
[0187] The prepared 2.5g LiFePO 4 (LFP) nanoparticles, KH-550 silane coupling agent (1.5wt%), ethanol (coupling agent: ethanol = 1.51:100) were slowly added to a high-speed mixer, stirred for 10-15min, and then dried at 95°C for 2h to complete the surface treatment of the nanoparticles, and then blended with 1.25g PMMA, ethanol and compatibilizer polycaprolactone to obtain LFP / PMMA composite materials. The coating of conductive carbon is the same as in Example 4.
[0188] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that the positive electrode material does not include a sustained-release layer; the preparation method of Comparative Example 2 is basically the same as that of Example 4, except that the positive electrode material does not include a sustained-release layer; the preparation method of Comparative Example 3 is basically the same as that of Example 3, except that Comparative Example 3 does not include a sustained-release layer.
[0189] 2. Test Method
[0190] 1) High temperature and high rate cycle performance
[0191] At 60°C, the lithium-ion battery is first charged at a constant current of 1C (i.e., the current value that completely discharges the theoretical capacity within 1 hour) to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C. After standing for 5 minutes, the lithium-ion battery is discharged at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The lithium-ion battery is subjected to multiple cycle charge and discharge tests according to the above method, and the discharge capacity of the 500th cycle is detected.
[0192] The capacity retention rate of the lithium ion battery after 500 cycles at 60° C. = (discharge capacity at the 500th cycle / discharge capacity at the first cycle)×100%.
[0193] 2) Viscosity test
[0194] Use a rotating viscometer to measure the viscosity of the electrolyte. Select a suitable rotor, fix the viscometer rotor, place the electrolyte before the cycle and the electrolyte after 500 cycles under the viscometer rotor, and the electrolyte just submerges the scale line of the rotor. Instrument model: Shanghai Fangrui NDJ-5S, rotor is 62#, the speed is 30 rpm, and the measurable viscosity range is 0-1000mPa·s; rotor is 63#, the speed is 30 rpm, and the measurable viscosity range is 0-2000mPa·s), test temperature: 25℃, test time is 5 minutes, and read the data after the display is stable.
[0195] 3) Solubility parameter test
[0196] The solubility parameter is measured by the intrinsic viscosity method. Solvents with different solubility parameter values are prepared, and the intrinsic viscosity of the sustained-release polymer in these solvents is measured respectively. The intrinsic viscosity and the solubility parameter of the corresponding solvent are plotted, and the solubility parameter value corresponding to the maximum intrinsic viscosity is taken as the solubility parameter value of the polymer.
[0197] The positive electrode composite material was cut by ion beam to obtain a flat cross section of the positive electrode active material particles, and a scanning electron microscope and image processing software were used to collect and analyze images to measure the particle size of the positive electrode active material, the particle size of the positive electrode composite material, and the thickness of the sustained release layer. The long diameter of the particle was taken as the particle size, and the sum of the particle sizes divided by the total number of particles was taken as the average particle size.
[0198] III. Analysis of test results of various embodiments and comparative examples
[0199] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in Table 1 below.
[0200] Table 1
[0201]
[0202] From the comparison between Examples 1-17 and Comparative Example 1, it can be seen that the positive electrode composite material includes a positive electrode active material and a sustained release layer at least partially coated on the surface of the positive electrode active material, and the sustained release layer includes a sustained release polymer that can be dissolved in the electrolyte, which is beneficial to improving the cycle stability of the battery.
[0203] It can be seen from Examples 1-4 that the positive electrode composite material further includes a conductive layer at least partially attached to the surface of the sustained-release layer, which can further improve the cycle stability of the battery.
[0204] It can be seen from Examples 1-4 that, compared with other conductive materials, graphene can further significantly improve the cycle stability of the battery.
[0205] It can be seen from Examples 5-8 that the average particle size of the positive electrode active material is 60nm-200nm, which can effectively improve the cycle stability of the battery. When the average particle size of the positive electrode active material is 80nm-120nm, the cycle stability of the battery is further improved.
[0206] It can be seen from Examples 9-12 that the thickness of the sustained-release layer is 10nm-20nm, which can effectively improve the cycle stability of the battery. When the thickness of the sustained-release layer is 13nm-18nm, the cycle stability of the battery is further improved.
[0207] The absolute value of the difference between the solubility parameter of the slow-release polymer in Examples 1-17 and the electrolyte solvent at 20°C to 25°C is less than 2J. 1 / 2 / cm 3 / 2 The slow-release polymer has good compatibility with the electrolyte, which is beneficial to improving the cycle stability of the battery.
[0208] It can be seen from Examples 1-17 that, along with the cycle reaction of the battery, the slow-release polymer gradually dissolves in the electrolyte, causing the viscosity of the electrolyte to increase.
[0209] From the comparison between Example 1 and Example 17, it can be seen that the in-situ grown slow-release polymer has better binding force with the positive electrode active material and has better slow-release effect than mechanical coating, which is beneficial to improving the cycle stability of the battery.
[0210] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode composite material, characterized in that: The invention comprises a positive electrode active material and a sustained-release layer at least partially coated on the surface of the positive electrode active material, wherein the sustained-release layer comprises a sustained-release polymer, and the sustained-release polymer comprises at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group.
2. The positive electrode composite material according to claim 1, characterized in that: The sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether or polydimethylsiloxane.
3. The positive electrode composite material according to claim 1 or 2, characterized in that: The ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode composite material is 0.55-0.
90.
4. The cathode composite material according to any one of claims 1 to 3, characterized in that: The average particle size of the positive electrode active material is 60nm-200nm, and can be 80nm-120nm.
5. The cathode composite material according to any one of claims 1 to 4, characterized in that: The thickness of the sustained-release layer is 10nm-20nm, and can be optionally 13nm-18nm.
6. The cathode composite material according to any one of claims 1 to 5, characterized in that: The slow-release polymer is in-situ grown on the surface of the positive electrode active material.
7. The cathode composite material according to any one of claims 1 to 6, characterized in that: The positive electrode composite material includes a conductive layer at least partially coated on the surface of the sustained-release layer.
8. The cathode composite material according to any one of claims 1 to 7, characterized in that: Based on the total mass of the positive electrode composite material, the mass percentage of the conductive layer is 4%-15%, and can be 6%-12%.
9. The cathode composite material according to any one of claims 1 to 8, characterized in that: The conductive layer includes graphene.
10. A method for preparing a positive electrode composite material, characterized in that: The preparation method comprises the following steps: Providing positive electrode active material, A sustained-release polymer is coated on at least a portion of the surface of the positive electrode active material to obtain a positive electrode composite material; wherein the sustained-release polymer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group.
11. The preparation method according to claim 10, characterized in that: The method comprises coating a slow-release polymer on at least a portion of the surface of the positive electrode active material, comprising: An emulsifier, an aqueous solvent, an oily solvent, a positive electrode active material, an initiator and a monomer are mixed and emulsion polymerization is performed to obtain an emulsion of the positive electrode composite material, wherein the monomer includes at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group.
12. The preparation method according to claim 10 or 11, characterized in that: The preparation method further comprises the following steps: At least a portion of the surface of the sustained-release polymer is coated with a conductive layer.
13. A secondary battery, characterized in that: The invention comprises a positive electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode composite material, wherein the positive electrode composite material comprises a positive electrode active material and a sustained-release layer at least partially coated on the surface of the positive electrode active material, wherein the sustained-release layer comprises a sustained-release polymer, wherein the sustained-release polymer comprises at least one of an ester group, an ether bond, a cyano group, a benzene ring or a siloxy group, and wherein the sustained-release polymer can be dissolved in the electrolyte during the cycle of the secondary battery.
14. The secondary battery according to claim 13, characterized in that: The slow-release polymer includes an ester group, and the electrolyte includes an ester solvent.
15. The secondary battery according to claim 13 or 14, characterized in that: At 20°C to 25°C, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no more than 2J 1 / 2 / cm 3 / 2 .
16. The secondary battery according to any one of claims 13 to 15, characterized in that: The sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, polystyrene, perfluoropolyether or polydimethylsiloxane.
17. The secondary battery according to any one of claims 13 to 16, characterized in that: The viscosity of the electrolyte is 0.8 mPa·s-1.50 mPa·s, and can be optionally 1.03 mPa·s-1.09 mPa·s.
18. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 13 to 17.
Citation Information
Patent Citations
Buffer layer for sulfide solid-state battery, preparation method of buffer layer, and solid-state battery
CN110034275A
Secondary battery
CN112420998A
Coated positive electrode material capable of slowly releasing oxygen as well as preparation method and application of coated positive electrode material
CN113517429A
Cathode material capable of slowly releasing oxygen as well as preparation method and application of cathode material
CN114142008A
Positive pole piece of lithium ion battery, preparation method of positive pole piece and lithium ion battery
CN114204027A
